Study of the Characteristic of Artificial Dryer for Vanilla Processing - S., Sumardi H.; Rakhmadiono, S.; Sinawang, T. A. (Fakultas Teknologi Pertanian Universitas Brawijaya, 2001)
Vanilla processing has four main steps: withering, sweating, drying and aging. Quite often, sweating and drying becomes obstacle to farmers; while the most affecting step to vanilla quality is drying. The aim of this research is to find out the characteristic and efficiency of vanilla dryer.Basic computation in this research is using 2000 kgs vanilla 88.73% moisture content and being sweated at 40oC every 5 hour each day for 6 days to reach 83.4% moisture content. After that it is dried at 50oC every 5 hour/day for 6 days to reach 30%.Fuel consumption is as much as 0.5 kg/h so the total heat energy yielded by fuel combustion (LHV) is 1,506,122.80 kJ. The energy is used to heat the drying room as much as 332,927.41 kJ. The heating energy is used for material drying as much as 256,855.06 kJ, thus the total energy efficiency of the artificial dryer for vanilla processing is 22.10% and drying efficiency is 17.05%.Keywords: vanilla fruit, artificial dryer